(untitled) (UNIZIK Journal of Educational Management and Policy, 2025)
This study investigated Artificial Intelligence tools as correlate of the implementation of Economics of Education curriculum in public tertiary institutions in Anambra State, Nigeria. To guide the study, two research questions were raised and two hypotheses were formulated and tested at 0.05 level of significance. The study adopted a correlational research design involving simple linear method. The population of the study is 2,657 lecturers from 9 tertiary institutions in Anambra State. A sample of 133 Economics of Education lecturers from 5 selected tertiary institutions offering Economics of Education in the study area was determined through Taro Yamane formula using purposive sampling technique. The research instruments used were two rating scales titled: Artificial Intelligence Tools Scale (AITS) and Implementation of Economics of Education Curriculum Scale (IEECS) which contained 20 items and 10 items respectively. The instruments were validated by five research experts. Reliability coefficients of 0.88 for AITS and 0.83 for IEECS were obtained using Cronbach Alpha statistics. Pearson Product Moment Correlation Coefficient (PPMCC) was used to answer the research questions while the hypotheses were tested using t-test of the significance of Pearson “r” statistics. The result revealed that intelligent tutoring systems and chatbots as AI tools have substantial and positive significant coefficient of relationship with the implementation of Economics of Education curriculum in tertiary institutions in Anambra State. It was concluded that institutions and lecturers who leverage on intelligent tutoring systems and chatbots can optimize curriculum delivery, reduce workload, and focus on high impact teaching activities. It was recommended amongst others that intelligent tutoring system as AI tool has a substantial and positive significant coefficient of relationship with the implementation of Economics of Education curriculum in tertiary institutions in Anambra State.